2010
DOI: 10.1155/2010/691425
|View full text |Cite
|
Sign up to set email alerts
|

FeNO as a Marker of Airways Inflammation: The Possible Implications in Childhood Asthma Management

Abstract: The aim of this study was to verify FeNO usefulness, as a marker of bronchial inflammation, in the assessment of therapeutic management of childhood asthma. We performed a prospective 1-year randomized clinical trial evaluating two groups of 32 children with allergic asthma: “GINA group”, in which therapy was assessed only by GINA guidelines and “FeNO group”, who followed a therapeutic program assessed also on FeNO measurements. Asthma Severity score (ASs), Asthma Exacerbation Frequency (AEf), and Asthma Thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
75
2
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(80 citation statements)
references
References 30 publications
2
75
2
1
Order By: Relevance
“…In one RCT, FeNO concentrations in adolescents with adherence of more than 50 percent of assigned doses of mostly ICS (measured using a built-in dose counter and a structured questionnaire) was 24 ppb compared to 31ppb in those with <50 percent adherence. 114 A second study in children demonstrated that FeNO values were associated with adherence to inhaled budesonide (r 2 =0.59) as assessed using dose counters 115 . A third study also in children showed that high FeNO level (>25 ppb) was associated with lower adherence rates to any asthma medication using the parental reported Medication Adherence Report Scale (OR: 0.4; 95% CI: 0.3-0.6).…”
Section: Using Feno To Monitor Adherence To Therapymentioning
confidence: 99%
“…In one RCT, FeNO concentrations in adolescents with adherence of more than 50 percent of assigned doses of mostly ICS (measured using a built-in dose counter and a structured questionnaire) was 24 ppb compared to 31ppb in those with <50 percent adherence. 114 A second study in children demonstrated that FeNO values were associated with adherence to inhaled budesonide (r 2 =0.59) as assessed using dose counters 115 . A third study also in children showed that high FeNO level (>25 ppb) was associated with lower adherence rates to any asthma medication using the parental reported Medication Adherence Report Scale (OR: 0.4; 95% CI: 0.3-0.6).…”
Section: Using Feno To Monitor Adherence To Therapymentioning
confidence: 99%
“…Fritsch et al 103 did not report the reasons for participant withdrawal or correction for missing FeNO values and there may have been missing outcome data in the study by Petsky et al, 107 but this is unknown as only a conference abstract of this study was identified. In the study by Verini et al 105 it was reported that 64 patients were recruited; however, it was unclear whether this was the total number after dropout or whether no participants dropped out. Consequently, the study was rated as 'unclear' on outcome data completeness.…”
Section: Risk Of Attrition Biasmentioning
confidence: 99%
“…In the study by Fritsch et al, 103 medication usage was reported as median (IQR) values rather than mean values and so these values could not be used in the planned meta-analysis; however, although planned, a meta-analysis was not possible because of study heterogeneity and so this bias did not affect the synthesis of data. The study by Verini et al 105 was rated as having a low risk of bias for selective reporting; respiratory function and immunoallergological parameters were inadequately reported (i.e. no numerical data were provided; it was stated only that there were no significant between-group differences on these outcomes), but these outcomes were not of relevance to this review.…”
Section: Risk Of Attrition Biasmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Accordingly, FeNO has gained substantial clinical and scientific interest since it is seen as a safer and less invasive alternative tool to bronchoscopy or induced sputum for diagnosis, monitoring, or predicting the response to the treatment of airway inflammation, especially in children. 3 Therefore, this review focuses on the clinical application of FeNO in children with allergic airway disease and the environmental and other factors that need to be considered when interpreting the results from FeNO measurements. and activity of the enzymes responsible for producing NO, the concentration of substrates, the level of oxidative stress and its rate of uptake by antioxidant molecules (Fig.…”
Section: Introductionmentioning
confidence: 99%